2016
DOI: 10.3324/haematol.2015.135475
|View full text |Cite
|
Sign up to set email alerts
|

Whole exome sequencing in families at high risk for Hodgkin lymphoma: identification of a predisposing mutation in the KDR gene

Abstract: H odgkin lymphoma shows strong familial aggregation but no major susceptibility genes have been identified to date. The goal of this study was to identify high-penetrance variants using whole exome sequencing in 17 Hodgkin lymphoma prone families with three or more affected cases or obligate carriers (69 individuals), followed by targeted sequencing in an additional 48 smaller HL families (80 individuals). Alignment and variant calling were performed using standard methods. Dominantly segregating, rare, coding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 39 publications
(50 reference statements)
0
39
0
Order By: Relevance
“…However, the variant may be associated with other lymphoid malignancies because we found the same variant segregating with Hodgkin lymphoma in 1 family. 5 The finding that all 3 of the unrelated clinic patients who were carriers of the variant had a family history is striking because previous studies found 12% to 17% of patients from CLL clinic populations have such a family history. 9,10 The cell surface marker, CD18, coded by the ITGB2 gene is expressed on lymphocytes and is involved in leukocyte adhesion.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…However, the variant may be associated with other lymphoid malignancies because we found the same variant segregating with Hodgkin lymphoma in 1 family. 5 The finding that all 3 of the unrelated clinic patients who were carriers of the variant had a family history is striking because previous studies found 12% to 17% of patients from CLL clinic populations have such a family history. 9,10 The cell surface marker, CD18, coded by the ITGB2 gene is expressed on lymphocytes and is involved in leukocyte adhesion.…”
mentioning
confidence: 86%
“…The study includes a total of 59 CLL-prone families (20 for discovery and 39 for replication; supplemental Table 1, available on the Blood Web site) and 173 unrelated CLL clinic patients unselected for family history. The clinical, laboratory, and bioinformatics methods were described previously 5 and are summarized in the supplemental Methods. For each family, we filtered variants to consider only those segregating with illness with population allele frequency ,1%.…”
mentioning
confidence: 99%
“…Germ line analysis is also imperative for: (1) biallelic CEBPA, as 7% to 11% of these individuals possess germ line CEBPA mutations 55,56 ; (2) a deleterious GATA2 mutation, especially in children/adolescents with MDS, as germ line GATA2 mutations are present in 7% of these cases overall and up to 72% of patients with monosomy 7 (many of these will be de novo germ line mutations with no family history or clinical features [ Families clustering mixed myeloid and lymphoid malignancies or lymphoid malignancies alone are more challenging, as the genes responsible for the majority of these families are largely unknown, although a pathogenic germ line variant of the KDR gene is associated with familial Hodgkin lymphoma. 61 We consider clinical testing for these families on a case-by-case basis based on specific HMMS patterns. For example, we do not routinely test families with familial chronic lymphocytic leukemia, but we do offer testing for families with AML segregating with T-cell acute lymphoblastic leukemia or follicular lymphoma, as these patterns may reflect HMMS (Table 1).…”
Section: Case 1 (Continued)mentioning
confidence: 99%
“…Our study does serve to provide a necessary sequel to the study of Goldin et al, as the evaluation of a disease-associated variant in multiple cohorts is required to establish a new genetic cause of disease, as outlined in guidelines produced by MacArthur et al 12 We propose that the current conflicting findings of the rs2230531 in familial HMs, together with the biological role of ITGB2 in blood cells, creates an a priori hypothesis that genetic variation in ITGB2 contributes to HM 4 RNA, 4 and polyphosphate (polyP). 5 Contributions of extracellular nucleic acids to coagulation and inflammation are under intense investigation, with several studies reporting the procoagulant effects of DNA, [6][7][8] particularly in the context of neutrophil extracellular traps (NETs). [9][10][11] In this study, we attempted to compare the clotting activity of polyP versus cellular DNA.…”
mentioning
confidence: 99%
“…Additionally, Rotunno et al have previously reported this variant in a whole-exome sequencing study of familial Hodgkin lymphoma. 6 Here, we examine the ITGB2 variant rs2230531 in an independent cohort of HMs from the Tasmanian Familial Hematological Malignancies Study (TFHMS). Our aim was to follow up the findings of Goldin et al in relation to the role of this variant in the genetic predisposition to HMs.…”
mentioning
confidence: 99%